2012
DOI: 10.1074/jbc.m111.309880
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes Regulate Expression of Pyk2 Isoforms and Caspase-mediated Cleavage of Actin in Osteoblasts

Abstract: Background: Osteoblast proliferation and differentiation are critical for bone formation. Results: Megakaryocytes increase osteoblast number and BrdU incorporation and induce cytoskeletal remodeling and the differential expression of Pyk2 isoforms in osteoblasts. Conclusion: Megakaryocytes stimulate osteoblast proliferation and alter the ratio of alternatively spliced Pyk2 isoforms. Significance: Pyk2 may be an important target for treatments aimed at increasing skeletal bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 64 publications
4
45
0
Order By: Relevance
“…21 Fetuses were dissected from pregnant mice at embryonic day 13-15. The livers were removed, and single-cell suspensions were made by forcing cells through sequentially smaller gauge needles (18,20, and 23 gauge).…”
Section: Preparation Of Fetal Liver-derived Megakaryocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Fetuses were dissected from pregnant mice at embryonic day 13-15. The livers were removed, and single-cell suspensions were made by forcing cells through sequentially smaller gauge needles (18,20, and 23 gauge).…”
Section: Preparation Of Fetal Liver-derived Megakaryocytesmentioning
confidence: 99%
“…21 Calvariae from 2-to 3-day-old neonatal mice were pretreated with 10 mM EDTA in phosphate-buffered saline (PBS) for 30 minutes. Calvariae were then subjected to sequential collagenase digestions (200 U/mL; Collagenase, Type 2, Worthington Biochemicals, Lakewood NJ).…”
Section: Preparation Of Fresh Nccsmentioning
confidence: 99%
“…Our group as well as others have been working to understand how MKs regulate bone mass. We previously reported that MKs, co-cultured with OBs, were able to stimulate OB proliferation (Kacena, et al, 2004, Ciovacco, et al, 2009, Ciovacco, et al, 2010, Lemieux, et al, 2010, Kacena, et al, 2012, Cheng, et al, 2013). Of note, Miao et al (Miao, et al, 2004) demonstrated the bone marrow stromal cell aggregates containing MKs expressed higher levels of alkaline phosphatase than did single cell suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…Surviving host MKs migrate to endosteal surfaces in bone where they stimulate a 2-fold increase in OB number thus augmenting the so-called endosteal hematopoietic stem cell niches. Contact between MKs and OBs and/or their precursors have been described (Cheng, et al, 2000, Miao, et al, 2004, Kacena, et al, 2004, Ciovacco, et al, 2009, Ciovacco, et al, 2010, Lemieux, et al, 2010, Dominici, et al, 2009, Kacena, et al, 2012, Cheng, et al, 2013). As an example, Cheng et al (Cheng, et al, 2000) observed that when isolating bone marrow stromal cells (BMSCs), complexes existed consisting of BMSCs and MKs, demonstrating a physical association between these cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, work from Boutahar and Sonomura have explored the theory that mechanical stimulation activates Pyk2 signaling in osteoblasts and renal tubular epithelial cells [20, 21]. Furthermore, Pyk2 was identified to affect cell proliferation in several cell types in response to many different stimuli [22, 23]. However, the special functions of Pyk2 in the process of mechanotransduced signal pathways in chondrocytes were completely unknown.…”
Section: Introductionmentioning
confidence: 99%